Analisis Efek Underreaction pada Saham Indofood: Pengaruh Sentimen Pasar dan Perilaku Investor - Irawan, Rini Larasati; Gurhanawan, Gurhanawan (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to identify the effects of underreaction on the stock of Indofood Sukses Makmur Tbk (INDF) by examining the influence of market sentiment and investor behavior on stock prices. The research employs a quantitative approach using secondary data analysis, utilizing stock price data, financial statements, and economic news related to Indofood sourced from the Indonesia Stock Exchange (IDX) and various news outlets. Data collection techniques include technical information such as daily closing prices and trading volumes, as well as fundamental data like income statements and balance sheets, complemented by market sentiment analysis from relevant economic news. Data analysis is conducted through linear regression to measure the relationship between market sentiment as the independent variable and INDF returns as the dependent variable, along with an event study approach to assess stock price reactions to new information, such as earnings announcements. This study also calculates the alpha and beta of the stock to evaluate INDF's performance and sensitivity to market movements, finding a positive correlation of 0.296 between INDF returns and the Composite Index (IHSG), with a significance value (p-value) of 0.000, indicating a statistically significant relationship, albeit weak. The findings reveal that INDF’s cumulative returns have decreased by -3.37%, while stock volatility is recorded at 1.33%, higher than the IHSG’s 0.84%. These results indicate the presence of underreaction, where stock prices do not respond promptly to new information, creating opportunities for momentum trading strategies that capitalize on market delays. This study provides insights into the dynamics of the Indonesian stock market and the relevance of market sentiment in developing investment strategies.